Histamine and Tyramine Content of South African Wine - Cilliers, J. D.; Van Wyk, C. J. (South African Journal of Enology and Viticulture, 2017)
The histamine content of 184 wines and tyramine content of 156 wines, produced in South Africa was measured. The histamine and tyramine content of the wine was found to be similar to those of wines produced in other countries. The average histamine content of South African red wines that had undergone malo-lactic fermentation was more than double that of red wines that had not undergone malo-lactic fermentation. All the red wines containing relatively large amounts of histamine had pH's above 3, 7. Six selected strains of malo-lactic bacteria were tested for their ability to form histamine and tyramine in white and red wine. No histamine or tyramine was formed.